Ketidakpastian Lingkungan dan Perubahan Strategis Perusahaan - Dirga Arya Farmansyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to examine the influence of environmental uncertainty on strategic changes in companies. The sample used consists of 386 data from manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021. The analysis technique used is moderated regression analysis using SPSS 26. The research results indicate that environmental uncertainty has a positive and significant effect on strategic changes in companies.